Embarazo y litiasis biliar. Especial referencia a la colecistectomía laparascópica - Llosa Tejada, Raúl (Revista Médica Herediana, 2013)
In this paper we review the indications of the laparoscopic cholecistectomy and other related methods in the diagnosis and treatment of cholelithiasis and choledocolithiasis during pregnancy. The epidemiology and ethiopathogenesis of biliary during pregnancy are also reviewed.